Learning Achievement in Computer Science on Threats in the Digital World Using Infographic Media for Prathomsuksa 4 Students at School Under the Ratchaburi Primary Education Service Area 2 - Thongsat, Jiraphorn; Somboon, Tanadol; Wongsan, Weera (Journal of Education Rajabhat Maha Sarakham University, 2025)
The objectives of this research were: 1) to develop learning achievement in Computer Science on Threats in the Digital World using Infographic Media with the criterion of 80%; 2) to determine learning progress in Computer Science on Threats in the Digital World by using Infographic Media; 3) to compare learning achievement in Computer Science on Threats in the Digital World between using Infographic Media and traditional teaching; and 4) to compare students’ satisfaction toward learning in Computer Science on Threats in the Digital World between using Infographic Media and traditional teaching. This research employed a quasi-experimental research design. The sample group was 50 of Prathomsuksa 4 students in the second semester of the academic year 2023 at school under the Ratchaburi primary education service area 2, was obtained via cluster random sampling method. The data collection instruments were: 1) learning materials on Threats in the Digital World; 2) infographic media on Threats in the Digital World; 3) lesson plan of Computer Science on Threats in the Digital World; 4) learning achievement test; and 5) students’ satisfaction questionnaire. Data analysis statistics were mean, Standard Deviation and percentage. Research findings were: (1) learning achievement in Computer Science on Threats in the Digital World using Infographic Media was 84.60%, which met the criterion of 80%; (2) learning progress in Computer Science on Threats in the Digital World using Infographic Media was 0.66, in medium gain; (3) learning achievement in Computer Science on Threats in the Digital World using Infographic Media was higher than traditional teaching; and (4) students’ satisfaction toward learning in Computer Science on Threats in the Digital World using Infographic Media was higher than traditional teaching.